Emissions of CH4 and CO2 from Wastewater of Palm Oil Mills: A Real Contribution to Increase the Greenhouse Gas and Its Potential as Renewable Energy Sources: 10.32526/ennrj/20/202100149 - Putro, Ledis Heru Saryono (Environment and Natural Resources Journal, 2021)
Palm oil mill effluent (POME) treatment in Indonesia is still predominant using an open pond system. This system has the weakness of the unknown and uncontrollable value of greenhouse gas (GHG) emissions into the atmosphere. This study estimated GHG emissions (CH4 and CO2) from anaerobic ponds and their potential as a renewable energy source and obtain GHG emission conversion coefficients for each kg of COD POME and ton of crude palm oil (CPO). Gas samples were collected using a closed static chamber. GHG sample concentration testing was done using Gas Chromatography with a flame ionization detector (FID) and thermal conductivity detector (TCD). The results showed that the emission rate of CH4 and CO2 in the anaerobic pond POME treatment was relatively high, 261.93 and 595.99 g/m2/day, respectively, equivalent to 48.572 t CO2-eq/day or 14,571.5 t CO2-eq/year. CO2 emissions were greater than two times CH4 emissions, both spatially and temporally. There was a process of facultative biodegradation, aerobic and or anaerobic process according to the biotic-abiotic environment and the levels of organic components in the substrate. In anaerobic ponds, the optimal requirements for the biodegradation process tended to be unfulfilled, so the emission rate of CH4 was less than CO2. The GHG conversion coefficient was obtained, namely each kg of COD from POME emitted 6.266 kg CO2-eq of GHG; for each m3 of POME emitted by 0.163 t CO2-eq of GHG; and 0.556 t CO2-eq/t CPO. The maximum potential for POME to energy conversion was 1.045 MWe with a power capacity of 8,603 MWh/year.